Modest Grief in the Office of the Dead: A Case Study of Emotion Terms in Translations of the Orthodox Funeral Vigil - Taras Shmiher (East European Journal of Psycholinguistics, 2022)
The aim of this paper is to consider the specific features of rendering ancient emotion terms and words connected with emotions into contemporary languages. The specific texts under study are the Great Litany and the prayer “God of all spirits and of all flesh” from the Byzantine Office for the Dead (its part is the Funeral Vigil): the Church Slavonic and Greek texts serve as the originals, and the translations are into Ukrainian, Polish and English. In religious contexts, ancient emotion terms usually contain psychic reactions and Christian associations which may have disappeared in modern usage. Besides, the emotions used in the funerary texts are never pathetic, but the positive and negative emotions are perfectly balanced. Special attention goes to the emotion of anger which acts as an ethical concept and serves as a synonym for divine punishment in mediaeval Slavonic cultures. The search for equivalents of emotion terms should go within two lines of reception: that of biblical lexis and that of patristic interpretation. Although the change of the meanings from physical rest to spiritual rest, death and other deathly associations is heavily dependent on the fundamentals of Christian theology, the exploration of the conceptual matrices of emotion terms discloses that even such universal emotions as fear and joy contain some space for the national interpretation of believers’ psychic states and the very Divinity. Moreover, translators have to remember that the conceptual matrix of emotion terms altered drastically after the Enlightenment, and the search for successful equivalents makes them insightful and creative.